PENGARUH PEMBERIAN REWARD DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR KELAS IV SD PUTRA BANGSA BERBUDI DELITUA - Parhusip, R.L Holmes; Sembiring, Hartono; Situngkir, Aderson; Simatupang, Genni Udurna; Ikhwani, Sabrina (Jurnal Ilmiah Aquinas, 2025)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-knowledge, personality, intelligence, morals The school environment is one of the strategic places where students are educated and fostered, in order to develop and cognitive, affective and psychomotor abilities through a series of learning program activities, habituation, extracurricular and other programs. For the improvement of noble education, as well as the skills needed by themselves, society, nation and state. Science or natural and social sciences is a branch of science that studies natural phenomena and the processes that occur around us, it covers various disciplines such as physics, chemistry, biology and astronomy, science focuses on understanding and applying scientific principles to explain and predict natural phenomena, predictions. Science subjects are also less in demand by students, therefore researchers need to make expectations for education through knowledge integration where emphasis is on combining concepts from the natural and social sciences to provide a more holistic and relevant understanding of global and local issues. The activities carried out in education are learning. "Learning is a conscious effort made by individuals to change behavior both through practice and experience related to cognitive, affective and psychomotor aspects". So learning activities are the most important activity in the educational process, and teachers must also be able to provide learning motivation to students in the learning process." As a final product of the learning process, learning outcomes are considered to be able to show what students have known and developed. "Learning outcomes are the abilities that students have Learning outcomes are the abilities that students have after they receive their learning experiences.